Neoadjuvant Treatment in Pancreatic Cancer - Oba, Atsushi; Ho, Felix; Bao, Quoc Riccardo; Al-Musawi, Mohammed H.; Schulick, Richard D.; Del Chiaro, Marco (Frontiers in Oncology, 2020)
Thanks to the development of modern chemotherapeutic regimens, survival after surgery for pancreatic ductal adenocarcinoma (PDAC) has improved and pancreatologists worldwide agree that the treatment of PDAC demands a multidisciplinary approach. Neoadjuvant treatment (NAT) plays a major role in the treatment of PDAC since only about 20% of patients are considered resectable at the time of diagnosis. Moreover, increasing data demonstrating the benefits of NAT for borderline resectable/locally advanced PDAC are driving a shift from up-front surgery to NAT in the multidisciplinary treatment of even resectable PDAC. Our understanding of the role of NAT in PDAC has evolved from tumor shrinkage to controlling potential micrometastases and selecting patients who may benefit from radical resection. The present review gives an overview on the current literature of NAT concepts for BR/LA PDAC and resectable PDAC.